2009
DOI: 10.1002/jmri.22016
|View full text |Cite
|
Sign up to set email alerts
|

Measuring aortic diameter with different MR techniques: Comparison of three‐dimensional (3D) navigated steady‐state free‐precession (SSFP), 3D contrast‐enhanced magnetic resonance angiography (CE‐MRA), 2D T2 black blood, and 2D cine SSFP

Abstract: Purpose: To compare nongated three-dimensional (3D) contrast-enhanced magnetic resonance angiography (CE-MRA) with 3D-navigated cardiac-gated steady-state free-precession bright blood (3D-nav SSFP) and noncontrast 2D techniques for ascending aorta dimension measurements.Materials and Methods: Twenty-five clinical exams were reviewed to evaluate the ascending aorta at 1.5T using: breathhold cine bright blood (SSFP), cardiac-triggered T2 black blood (T2 BB), axial 3D-nav SSFP, and nongated 3D CE-MRA. Three radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 18 publications
7
65
0
Order By: Relevance
“…Gated 3D contrast enhanced MRI is not straightforward, but may reduce this blurring. Two-dimensional techniques, as balanced turbo field echo cine bright blood and triggered T2 black blood have shown to allow for accurate determination of aortic diameter Groth et al (2011);Potthast et al (2010), but do not provide a 3D geometry. Three-Dimensional (3D) navigated Steady-State Free-Precession (SSFP) allows for 3D assessment of the geometry without contrast injection.…”
Section: Discussionmentioning
confidence: 99%
“…Gated 3D contrast enhanced MRI is not straightforward, but may reduce this blurring. Two-dimensional techniques, as balanced turbo field echo cine bright blood and triggered T2 black blood have shown to allow for accurate determination of aortic diameter Groth et al (2011);Potthast et al (2010), but do not provide a 3D geometry. Three-Dimensional (3D) navigated Steady-State Free-Precession (SSFP) allows for 3D assessment of the geometry without contrast injection.…”
Section: Discussionmentioning
confidence: 99%
“…When vessel wall analysis is desirable, as in aortic conditions such as mural hematoma, black-blood techniques may at times provide a better wall depiction than CE-MRA (Potthast, 2010;Litmanovich, 2009 as much signal as possible from flowing blood in the vessels lumen (Fig4). Luminal signal void occurs because intravascular protons only produce signal if they are exposed to both a 90-degree excitation pulse and subsequent refocusing pulse while travelling through the image slice.…”
Section: ''Black-blood" Mrmentioning
confidence: 99%
“…It allows the study of the extent of an aneurysm and its relationship to the aortic branches, with reproducible results (Prince, 1996;Krinsky, 1997;Debatin, 1998;Neimatallah, 1999). Breath-hold non ECG-gated CE-MRA is nevertheless more prone to motion artifacts and blurring at the aortic root, with potential implications for treatment planning (Potthast, 2010;Cigarroa, 1993). Non-contrast enhanced ECG-gated 3D-SSFP has shown good results in aneurysm imaging, providing good assessment of diameter, lumen patency and topographic evaluation, including the aortic root Potthast, 2010).…”
Section: Aortic Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have compared 2 D cine-MRI sequences with 3 D non-contrast MRI and revealed that the 2 D sequences had the highest interobserver correlation. However, after critical evaluation of their data, the authors stated that this might be due to the fact that the imaging plane for cine-MRI is prescribed at the time of the scan by the technologist and later measurements are performed at this same source plane by all readers leading to a good correlation [28]. Nevertheless, this limitation is the same for echocardiographic measurements, since echocardiographic imaging was performed once by one observer per patient in our study.…”
mentioning
confidence: 93%